2018
DOI: 10.1093/mnras/sty1186
|View full text |Cite
|
Sign up to set email alerts
|

mocca-survey Database I: Galactic globular clusters harbouring a black hole subsystem

Abstract: There have been increasing theoretical speculations and observational indications that certain globular clusters (GCs) could contain a sizeable population of stellar mass black holes (BHs). In this paper, we shortlist at least 29 Galactic GCs that could be hosting a subsystem of BHs (BHS). In a companion paper, we analysed results from a wide array of GC models (simulated with the MOCCA code for cluster simulations) that retained few tens to several hundreds of BHs at 12 Gyr and showed that the properties of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 77 publications
13
145
0
Order By: Relevance
“…This is a consequence of mass segregation and is consistent with predictions from a number of recent analyses (e.g. Kulkarni et al 1993;Sigurdsson 1993;Breen & Heggie 2013;Morscher et al 2015;Chatterjee et al 2017b;Askar et al 2018 models n8-rv0.5-rg8-z0.01, n8-rv1-rg8-z0.01, n8-rv2-rg8-z0.01, and n8-rv4-rg8-z0.01). Bottom: Time evolution of the theoretical core radii of these models.…”
Section: Radial Profilessupporting
confidence: 90%
See 1 more Smart Citation
“…This is a consequence of mass segregation and is consistent with predictions from a number of recent analyses (e.g. Kulkarni et al 1993;Sigurdsson 1993;Breen & Heggie 2013;Morscher et al 2015;Chatterjee et al 2017b;Askar et al 2018 models n8-rv0.5-rg8-z0.01, n8-rv1-rg8-z0.01, n8-rv2-rg8-z0.01, and n8-rv4-rg8-z0.01). Bottom: Time evolution of the theoretical core radii of these models.…”
Section: Radial Profilessupporting
confidence: 90%
“…Much of the recent theoretical work on GC dynamics has focused on the crucial role played by stellar black hole (BH) remnants in these systems. Several studies have shown that large numbers of stellar-mass BHs can be retained in typical GCs all the way to the present, and their dynamical interactions in the cluster core over its ∌ 12 Gyr of evolution provide a natural physical explanation for many of the diverse cluster features alluded arXiv:1911.00018v1 [astro-ph.HE] 31 Oct 2019 to in the previous paragraph (e.g., Morscher et al 2015;Mackey et al 2008;Breen & Heggie 2013;Askar et al 2018;Kremer et al 2019a). The first BH candidate in a cluster was identified in the extragalactic GC NGC 4472 by Maccarone et al (2007) through X-ray observations.…”
Section: Introductionmentioning
confidence: 99%
“…Strader et al (2012) detected two accreting stellar-mass black holes in this cluster using X-ray and radio observations which they named M22-VLA1 and -VLA2. Using numerical models and observational parameters of Galactic GCs, Askar et al (2018) predict that NGC 6656 harbours a population of about 30 stellar mass black holes giving rise to its large halflight radius of 1.3 pc (Harris 1996(Harris , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The number density n of scattering particles depends critically on the amount of NSs and BHs left in the cluster. For BHs, we exploit our recent studies on BH subsystems in GCs 22,23 . Using MOCCA models, we find that the typical density of the BH ensemble is comparable to the cluster density, nBH ≡ n ≈ MGC/(m* RGC 3 ).…”
Section: Methodsmentioning
confidence: 99%